Синкретизм предикативно-обставинних детермінантів: типологічні вияви та специфіка функціонування (на матеріалі сучасного газетного дискурсу) - Наливайко, Юлія; Nalyvaiko, Yuliia (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто специфіку функціонування детермінантів синкретичного типу в сучасному газетному дискурсі. Предметом дослідження стали основні форми реалізації синкретичної семантики детермінантним предикативно-обставинним компонентом із одночасним визначенням кваліфікаційних ознак цих синкретичних одиниць, а також їхня роль у формуванні адекватного сприйняття задуму автора реципієнтом.The paper continues series of publications devoted to pecularities of functioning syncretic determinants in the modern newspaper discourse. The article devoted to the problem of Syncretism in the System of the secondary parts of the sentence. This article is dedicated to the realization peculiarities of syncretism phenomenon in determinants. The author analyses the dominating formes of the syncretism semantics realization in the determinant components. The paper focuses on defining place of adverbial determinants in the syntactic synonym paradigm, represented by the constructions of various types, on the basis of the modern publicistic discourse. Qualification features of the predicative adverbial syncretic determinants as well as their role in the formation of literal perception of the author’s concept by the recipient are defined.
Sincretism of Predicative Adverbisl Determinants: Typology and Specificity of Functioning (Case Study of Newspaper Discours)
Keywords: синкретизм; предикативно-обставинний детермінант; семантична достатність; газетний дискурс; syncretism; predicative adverbial determinants; semantic sufficiency; newspaper discours